Elucidating ligand binding and channel gating mechanisms in pentameric ligand-gated ion channels by atomistic simulations. (7th April 2015) - Comitani, Federico; Melis, Claudio; Molteni, Carla
Abstract : Pentameric ligand-gated ion channels (pLGICs) are important biomolecules that mediate fast synaptic transmission. Their malfunctions are linked to serious neuronal disorders and they are major pharmaceutical targets; in invertebrates, they are involved in insecticide resistance. The complexity of pLGICs and the limited crystallographic information available prevent a detailed understanding of how they function. State-of-the-art computational techniques are therefore crucial to build an accurate picture at the atomic level of the mechanisms which drive the activation of pLGICs, complementing the available experimental data. We have used a series of simulation methods, including homology modelling, ligand–protein docking, density functional theory, molecular dynamics and metadynamics, a powerful scheme for accelerating rare events, with the guidance of mutagenesis electrophysiology experiments, to explore ligand-binding mechanisms, the effects of mutations and the potential role of a proline molecular switch for the gating of the ion channels. Results for the insect RDL receptor, the GABAC receptor, the 5-HT3 receptor and the nicotinic acetylcholine receptor will be reviewed.